Violência contra mulheres, saúde mental e a decisão sobre o registro do boletim de ocorrência: um estudo a partir das histórias de vida - Ripa, Rafaela (2024)
This research addresses violence against women, its relationship with their mental health, and the filing of police reports against perpetrators. Violence against women is understood as a severe violation of human rights and results in impacts on a biopsychosocial dimension. Experiencing numerous forms of violence and attempts of femicide has significant impacts on women’s mental health. The Maria da Penha Law was responsible for developing a System for Combating Domestic and Family Violence Against Women within Brazilian legislation. Among the main specialized services for addressing violence against women are the Specialized Police Stations for Women (DEAMs), a public facility considered the main entry point for women into the network of protection and combat against violence. Despite this, DEAMs also have various limitations that may restrict or prevent the realization of women's rights. Based on this reality, the objectives of this research were defined as investigating, through a literature review and life stories of women in situations of intimate partner violence, the decision to file a police report, the role of Psychology in this context, and the impacts on women’s mental health. To this end, two articles were developed. The first article, “Violence Against Women and the Possibilities of Psychological Practices in Women’s Police Stations,” consists of an integrative literature review aimed at mapping psychological practices developed in Women’s Police Stations and how such practices are evaluated by the women served. A search on the portals/bases Scielo, BVS, and Redalyc for full articles published since 2006 using the combined keywords: “psychology, police station, woman” returned 633 titles, of which 11 were selected for thematic analysis. The categories “Actions Developed by Psychologists and Their Benefits” and “Importance of the Involvement of Psychology Professionals in Specialized Police Stations for Women (DEAM)” were highlighted. The role of Psychology in this field appears undervalued and fraught with challenges regarding psychologist training and effective integration into police station teams. The second article, “Violence Against Women: Decision- Making for Filing a Police Report,” was developed from a field study aimed at understanding, through the life stories of women in domestic violence situations, the reasons involved in the decision to file a police report against the perpetrator. This qualitative study, based on thematic life history interviews with three women with a history of domestic violence, was conducted at the Specialized Police Station for Women in a municipality in Minas Gerais. Data analysis from interviews was inspired by Bardin's content analysis and highlighted four themes: “It wasn’t just one incident; he always yelled, was always aggressive”: the types of violence against women during relationships; “I thought a lot”: betrayal and physical violence as triggers for filing a police report against the partner; “They only listened with a lot of impatience”: initial service at the DEAM; “How hard it is to live in fear”: life after filing the report. The reports were made after a severe incident of physical violence, which could be considered the trigger for the complaint. However, violence was already present in the relationship (verbal, psychological, moral, property-related, and attempts of femicide). The impacts persisted after the report, extending to the children, highlighting the importance of psychological follow-up. Listening to and supporting the life stories of the participating women proved to be an invaluable tool for the research, as it allowed for contact with the uniqueness of each interviewee, understanding their trajectory, the history of their affective relationships, the experience of the violent marital relationship, the suffering and impacts caused, and the decision to report the perpetrator to end the cycle of violence. It was possible to see, by listening to the women, how much violence appeared in their narratives as they told their life stories, which can show how much violence occupied (and still can occupy) spaces in their lives. The literature review conducted and the experience gained in the field research allow for reflection on the reality of the services provided to women at women’s police stations and highlight numerous challenges for the proper insertion and role of psychologists in this context. It is necessary to stimulate discussions and develop more tools aimed at supporting qualified care that ensures the protection of women’s rights.